Audit of unplanned re-attendance to a paediatric emergency department. (24th May 2012) - Simmons, N; Syahanee, R; Marzouk, O; Grice, J
Abstract : Aims: This audit examines unplanned re-attendance at a Paediatric Emergency Department (ED) against a Department of Health Clinical Indicator published April 2011. This states we should aim 'To reduce avoidable re-attendances at A&E by improving the care and communication delivered during the original attendance'. Methods: Information regarding patients who attended the ED more than once in seven days was collected retrospectively using a proforma. The period studied was May 2011. Exclusion criteria were re-attendance on a planned date or with an unrelated condition. The aim was to collect data for at least 50 re-attendees. Work is ongoing, collecting information on a control group. Results: 51 of 91 re-attendees (56%) were eligible for inclusion. 30 of the 51 were under two years of age. Most re-attendances were within three days of initial attendance. Medical patients made up 82% of re-attendees. Injured patients made up the remainder. The most common presenting complaints amongst medical re-attendees were vomiting, pyrexia and diarrhoea. The most common final diagnosis was viral gastroenteritis. Most injured patients were diagnosed with soft tissue injury. 73% received intervention other than advice on first attendance. 59% had a change to management on re-attendance and this is explored. In the majority, appropriate advice had been given and documented. For 31% it had not. 22% of re-attendances were judged medically necessary. In a further 12% this was uncertain. 67% of re-attendances were felt not to have been medically necessary. It was felt that re-attendance could have been prevented by different treatment for 16% of patients and that further advice only could have prevented re-attendance for 41%. 55% of re-attendees had attended the same ED in the preceding six months. The most common reasons behind frequent attendance were identified as 'failure to use other services appropriately' (13 of the 28 frequent attenders) and 'anxious carer.' Conclusion: Just over half of re-attendances were unplanned. Many of these may be preventable by giving further advice on initial attendance. Most re-attendees had a history of frequent attendance. It may be appropriate to address the underlying causes behind this.